LYME DISEASE AND THE GREAT IMITATOR: DIFFERENTIAL DIAGNOSIS IN COMPLEX CLINICAL PRESENTATIONS. LITERATURE REVIEW - Karina Grzesik,; Katarzyna Pilarczyk,; Aleksandra Rabęda, (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: Lyme disease is a tick-borne zoonosis caused by the bacterium Borrelia burgdorferi, characterized by highly variable and often nonspecific manifestations. Its ability to mimic neurological, rheumatological, cardiological, and psychiatric disorders makes it a classic”great imitator.” The aim of this review is to summarize current knowledge on the differential diagnosis of Lyme disease and to highlight the risks associated with both under- and overdiagnosis.Brief description of the state of knowledge: Despite its prevalence, the literature rarely addresses Lyme disease comprehensively as a”great imitator.” Most studies focus on selected organ-specific manifestations, and reports of atypical or misleading cases are scarce. This review integrates data on symptoms—particularly neurological, rheumatological, and cardiological—providing a framework for understanding diagnostic challenges. It emphasizes the overlap of clinical presentations with other diseases and the limitations of current diagnostic methods, highlighting the need for more integrated approaches in clinical practice and research.Methods: A literature review was conducted using PubMed and Google Scholar withsearch terms like”Lyme disease", ”Lyme carditis", ”Lyme arthritis", ”Neuroborreliosis" and related variations. Articles published within the last five years were prioritized.Conclusions: Lyme disease should always be considered in patients with unexplained, multi-organ symptoms, but diagnosis must rely on rigorous clinical and laboratory criteria. Awareness of its ability to mimic other conditions is essential to avoid missed or misattributed diagnoses. Diagnostic vigilance and critical interpretation of results are key to optimizing patient care and preventing therapeutic errors.